Educating the Soul in the World of Algorithms: Islamic Philosophy of Education as a Critique of Secular Digital Humanism - ghufron, muhammad ghufron; sumardi, sumardi; dadang, Dadang Falah Mutaqin; Khoiriyah, Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to critically examine the dominance of algorithm-based education in the contemporary digital era and to reconstruct Islamic educational philosophy as a critical framework against secular digital humanism. The phenomenon addressed in this research is the increasing reliance on algorithms, artificial intelligence, and data-driven systems in education, which tend to reduce human beings to functional and measurable subjects while positioning education as a technical process oriented toward efficiency and performance. Such conditions marginalize the spiritual, moral, and existential dimensions of education. This study employs a qualitative philosophical approach using critical-conceptual analysis, drawing upon classical and contemporary sources in Islamic educational philosophy and digital education studies. The analysis focuses on the epistemological and ontological assumptions underlying secular digital humanism and contrasts them with key concepts in Islamic educational thought, such as tazkiyat al-nafs (purification of the soul), ta’dīb (formation of adab), and the ideal of insān kāmil. The findings reveal that Islamic educational philosophy functions not merely as a complementary value system but as a fundamental philosophical critique that challenges the reductionist logic of algorithmic education. This study further demonstrates that Islamic philosophy reorients educational goals by subordinating technology and algorithms to transcendental purposes centered on soul formation and moral integrity. The main contribution of this research lies in offering a humanistic–transcendental framework that enriches global discussions on digital education by integrating spiritual and ethical dimensions that are largely absent from mainstream secular approaches.